Graphene optical modulators using bound states in the continuum - Kim, Myunghwan; Kim, Sangin; Kim, Soeun (Scientific Reports, 2022)
Graphene-based optical modulators have been widely investigated due to the high mobility and tunable permittivity of graphene. However, achieving a high modulation depth with a low insertion loss is challenging owing to low graphene-light interaction. To date, only waveguide-type modulators have been extensively studied to improve light-graphene interaction, and few free-space type modulators have been demonstrated in the optical communication wavelength range. In this study, we propose two graphene-based optical free-space type modulators in a simple silicon photonic crystal structure that supports bound states in the continuum. The designed modulator with an ultra-high quality factor from the bound states in the continuum achieves a high modulation depth (MD = 0.9972) and low insertion loss (IL = 0.0034) with a small Fermi level change at the optical communication wavelength. In addition, the proposed modulators support outstanding modulation performance in the normal chemical vapor deposition (CVD) graphene (mobility = 0.5 m2/Vs). We believe the scheme may pave the way for graphene-based optical active devices.